Defining upper extremity dominance: The contributions of hand preference and grip strength - Mohamadreza Hatefi; Seyedeh Feriyal Mahdavi; Amirreza Abbasi; Farideh Babakhani (PLoS ONE, 2025)
Background Upper extremity (UE) dominance is often defined by self-reported hand preference; however, this may not accurately reflect true functional or strength-based dominance. This study examined the relationship between writing hand, throwing hand, and maximal grip strength to assess how these measures align. Methods Thirty-four healthy, recreationally active college-aged individuals reported their preferred writing and throwing hands and completed standardized grip strength testing. Associations among the variables were analyzed using Phi coefficients and chi-square tests. Results A moderate, significant relationship was found between writing and throwing hand preference (φ = 0.456; p = 0.008), indicating general consistency across these subjective measures. However, no significant association emerged between grip strength dominance and either writing (φ = 0.027; p = 0.876) or throwing hand (φ = 0.096; p = 0.574). Conclusion These results suggest that grip strength dominance may not correlate with commonly used indicators of hand preference, highlighting the need for task-specific definitions of dominance in clinical and athletic contexts. Consequently, employing such task-specific definitions allows for more accurate assessments and enhances the translational relevance of research findings in practical settings.